PENGARUH STABILITAS KEUANGAN DAN KOMITE AUDIT TERHADAP KECURANGAN LAPORAN KEUANGAN: Studi Empiris pada Perusahaan Industri Keuangan dan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2021 - Rafelius Waruwu; Andry Sugeng (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study discusses the effect of financial stability and the audit committee on financial statement fraud by selecting the object of the financial and banking industry sectors in Indonesia. The purpose of this study is to determine the effect of financial stability and the audit committee simultaneously on fraudulent financial statements; partial effect of financial stability on financial statement fraud; and the partial effect of the audit committee on financial statement fraud. The research method chosen is descriptive quantitative research method. The data used is secondary data with the retrieval technique using the documentation method. The sampling technique was carried out by purposive sampling on the considerations of certain criteria determined by the researcher. Then the data obtained were analyzed using descriptive statistical analysis methods, panel data models, panel data regression model selection test, classical assumption test, multiple linear regression test, and hypothesis testing. This study concludes that simultaneously financial stability and the audit committee have an effect on financial statement fraud. Likewise, the partial test results conclude that financial stability has an positive effect on financial statement fraud, and the audit committee has no effect on financial statement fraud.